Regulation of Apoptotic Cell Clearance During Resolution of Inflammation - Arienti, Simone; Barth, Nicole D.; Dorward, David A.; Rossi, Adriano G.; Dransfield, Ian (Frontiers in Pharmacology, 2019)
Programmed cell death (apoptosis) has an important role in the maintenance of tissue homeostasis as well as the progression and ultimate resolution of inflammation. During apoptosis, the cell undergoes morphological and biochemical changes (e.g. phosphatidylserine (PtdSer) exposure, caspase activation, changes in mitochondrial membrane potential and DNA cleavage) that act to shut down cellular function and mark the cell for phagocytic clearance. Tissue phagocytes bind and internalize apoptotic cells, bodies and vesicles, providing a mechanism for the safe disposal of apoptotic material. Phagocytic removal of apoptotic cells before they undergo secondary necrosis reduces the potential for bystander damage to adjacent tissue and importantly initiates signaling pathways within the phagocytic cell that act to dampen inflammation. In a pathological context, excessive apoptosis or failure to clear apoptotic material results in secondary necrosis with the release of pro-inflammatory intracellular contents. In this review, we consider some of the mechanisms by which phagocytosis of apoptotic cells can be controlled. We suggest that matching apoptotic cell load with the capacity for apoptotic cell clearance within tissues may be important for therapeutic strategies that target the apoptotic process for treatment of inflammatory disease.